ENVIRONMENTALLY SAFE CONTINUOUS CASTING OF HYPEREUTECTIC FINE-CRYSTALLINE SILUMIN INGOTS - V. Ju. Stetsenko; A. M. Pevnev; Suk-Bong Kang (Литьë и металлургия)
It is shown that continuous horizontal casting of alloy AK18 into jet crystallizer with application of flooded – jet systems of ingot cooling and hereditary modifying enables to create ecologically safe technological process of production of alloy AK18 ingots in diameter of 40 mm with dispersion of eutectic silicon crystals less than 20 mm.